O formalismo no direito e a ética dos valores: teoria dos valores em Hans Kelsen e Max Scheler - FONSECA, Yuri Ikeda (Universidade Federal do Pará, 2018)
The philosophy of values (Wertphilosophie), appearing in the context of the neo-Kantian investigations of the School of Baden in the late 19th Century, is a theoretical approach focused on the study of the phenomenon called value. The first chapter of this work, with the methodology of a history of ideas, discusses the formalist ethics of Immanuel Kant, the origin of the philosophy of values in the theories of Franz Brentano and neo-Kantians Hermann Lotze, Wilhelm Windelband, Heinrich Rickert and Emil Lask, and the division of the theory of values into an objectivist strand and a subjectivist one, trying to demonstrate that the latter has prevailed due to the influence of Friedrich Nietzsche's conceptions of values. The second chapter deals with Max Weber's idea of axiological neutrality (Wertfreiheit) of the sciences and Hans Kelsen's legal formalism, which is supported by a subjectivist and skeptical theory of values, both representing the subjectivist view. It is also presented Carlos Santiago Nino’s argument against the idea, defended by Kelsen, that only a relativistic conception of values could promote the democratic ideals of tolerance. The third chapter is dedicated, after a brief comment on Edmund Husserl's phenomenology, to Max Scheler's arguments against Kantian ethical formalism to support an objectivist axiology based on the notion that values are material contents that can be known a priori and are, therefore, capable of substantiating a nonformal ethic. It is concluded that, though Scheler’s statement of grounds is problematic in considering the knowledge of values as a function of emotions, not of reason, on the other hand his formulation of the a priori and of a scope of pure axiology with rules similar to those of logic facilitate objections to the presuppositions of the subjectivist axiology.